Total-internal-reflection-based optical rotation quasi-phase-matching for efficient second-harmonic generation in Cadmium Germanium Arsenide crystal - Snigdha Sinha; Dr.Sumita Deb; Dr. Minakshi Deb Barma; Dr. Sumita Deb; Susmita Paul (International Journal of Crystalline Materials, 2026)
This study investigates a total-internal-reflection (TIR)-based optical rotation quasi-phase-matching (ORQPM) approach for second harmonic generation within a cadmium germanium arsenide crystal slab. The crystal is coated with a thin film of yttrium oxide to facilitate precise control over phase shifts between p- and s-polarized light upon reflection at the slab-film interface. By leveraging the interplay between TIR- induced optical rotation and fractional QPM effects at designated bounce points, the configuration aims to maximize nonlinear interaction and conversion efficiency. Numerical simulations incorporating key optical losses—including surface roughness, material absorption, and interference effects arising from the nonlinear law of reflection—were conducted to assess performance. The resulting conversion efficiency for second harmonic output at 1.95 micrometer is determined to be 5.7%.
Keywords: Cadmium Germanium Arsenide crystal; Conversion Efficiency; ORQPM; Total Internal Reflection; Yttrium Oxide